METHOD OF DYNAMIC EXPRESSION OF UNCERTAINTY OF MEASUREMENT - O. M. Vasilevskyi (Приборы и методы измерений)
The way of expressing the dynamic uncertainty of measurement that allows using the spectral function of the input signal and the frequency response of the measurement tools used to assess the uncertainty in its dynamic operation.